1983
DOI: 10.1111/j.1651-2227.1983.tb09820.x
|View full text |Cite
|
Sign up to set email alerts
|

Lactation Performance of Mothers With Contrasting Nutritional Status in Rural Kenya

Abstract: Breastmilk yields and its composition during the first 6 months of lactation were measured in 46 women with low weight-for-height during the third trimester of pregnancy (WH minus group) and in 52 mothers with good weight-for-height in the same period (WH plus group). On average WH minus mothers produced 695 g per 24 hours and WH plus mothers 790 g. In the WH minus group yield was affected by feeding frequency, season, mother's energy intake during lactation and infant's weight-for-age. In the WH plus group fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 9 publications
3
12
1
Order By: Relevance
“…1), which is in agreement with previous studies [9][10][11]. The pair-fed group showed the highest transcript levels for h-casein and WAP, but the low-zinc group showed no effect on the expression of these proteins (Fig.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…1), which is in agreement with previous studies [9][10][11]. The pair-fed group showed the highest transcript levels for h-casein and WAP, but the low-zinc group showed no effect on the expression of these proteins (Fig.…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies [9][10][11]34] and the results of this study show that total milk protein concentration does not seem to be affected by suboptimal maternal nutrition. However, there are probably situations when some specific proteins increase and others decrease in concentration, although not significantly affecting total protein concentration in the milk [35,36].…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…Indeed, there are very few data on the nutritional value of breast milk during prolonged (Ͼ1-year) lactation. A Medline search using the key words "lactation" or "breast milk" or "human milk" or "breastfeeding" and "duration" and "composition" revealed only 8 articles, of which 7 originated from developing countries [15][16][17][18][19][20][21] and only 2 dealt with issues of milk composition. 20,21 The largest study on the topic, by Dewey et al, 22 found that "fat .…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of information on the distribution of body mass index in Australian women35 it was estimated that a sample of at least 300 breast feeding women was required to detect a relative risk of 1 5 for earlier cessation of breast feeding, with 80% power and a significance level of 5%, in women with a body mass index above 25 compared with those with one in the normal range (20)(21)(22)(23)(24)(25). In order to obtain a group of this size, all women whose first infant was born between May 1 1984 and April 30 1985, who chose to breast feed and who were attending an infant welfare centre in the Barwon region of Victoria were invited to participate in the study.…”
Section: Study Populationmentioning
confidence: 99%